Cost And Time Performance Analysis Of The Ru Guest House And Main House Construction Project Using The Earned Value Method - Komang Gede Triska Bayu Wedananta; Hanie Teki Tjendani; Budi Witjaksana (Syntax Corporation Indonesia, 2025)
The construction project of Rumah Ru Guest House and Main House experienced delays due to a lack of careful initial planning and narrow access roads that hampered the delivery of materials. These obstacles affected the overall construction progress. To overcome these problems, the Earned Value Method (EVM) was used to analyze project performance in terms of cost and time. EVM uses three main indicators, namely Actual Cost of Work Performed (ACWP), Budgeted Cost of Work Performed (BCWP), and Budgeted Cost of Work Scheduled (BCWS). The research data was obtained from the executing contractor, CV. Cipta Karya Utama. The results of the analysis show that the project performance in week 15 to week 21 experienced problems, indicated by negative values in Schedule Variance (SV) and Cost Variance (CV). This reflects the delay of work from the planned schedule and cost overruns. In addition, the Schedule Performance Index (SPI) and Cost Performance Index (CPI) values of less than 1 also confirm that the project's time and cost performance is not optimal. These findings emphasize the need for improvement in future project planning, particularly in anticipating logistical barriers and managing resources for more efficient project performance